Katherine Dunham and Peronism: An Analysis of Dunham's Tango (1954) - Cadús, María Eugenia (2018)
Through close analysis of primary and secondary source material related to Katherine Dunham's Tango (1954), this article examines the protest message of this dance work within the political and social context of the time. The article focuses first on Dunham's understanding of the Argentine populist political movement known as Peronism, and secondly on the Argentine reception of the piece's protest against Juan Domingo Perón's government. The article argues that, contrary to existing interpretations of the work, Tango articulated with the cultural policies promoted by Perón's government, rather than working as a protest performance against it.